Analisis Karakteristik Curah Hujan pada Kawasan Hunian dan Komersial Pantai Indah Kapuk (PIK) 2 Cluster “C” - Nur Afifah Sari; Etih Hartati; M. Candra Nugraha (Jurnal Serambi Engineering, 2020)
Based on the hydrological cycle, one of the main water sources is rainwater. weather or climate conditions that occur will greatly affect the nature and condition of a rain or rainy season. On a global scale, the existence of water naturally is constant, only occurs in variations both in time and space on a regional scale. Analysis of the rainfall characteristics of Pantai Indah Kapuk (PIK) residential and commercial areas 2  Cluster "C" in Tangerang Regency, Banten Province, is for to find out the intensity of rainfall used for drainage planning. The daily rainfall data used includes 5 rain catching stations with a duration of 25 years (1994 - 2018). The Van Breen method is used to process rainfall data within a certain period into rainfall intensity with various times for drainage planning used. In the planning of drainage channels the rainfall return period used is PUH 2 for tertiary lines with selected rainfall data of 192 mm / day and PUH 5 for secondary lines with selected rainfall data of 219 mm / day. The IDF curve shows that rainfall intensity is affected by the time and return period of rainfall, where the shorter the rainfall time and the greater the return period of rainfall, the higher the intensity of rainfall produced.